Influence of Blended Fine Aggregates on the Performance of Lime - Cement Mortar – A Statistical Approach - Arulmoly, B.; Konthesingha, C.; Nanayakkara, A. (IEEE, 2021)
—This study investigates the performance evaluation of lime-cement mortar comprised of manufactured sand and offshore sand as the river sand alternatives. The most common mortars suggested by the standards such as S and N types were selected and five mixes were prepared for each type. Different sand compositions such as river sand alone, manufactured sand alone and blended sand with manufactured sand and offshore sand were used in the mixes. The performance of mortars with sand replacements were investigated based on the fresh and hardened properties. The experimental results were undergone for one-way analysis of variance (ANOVA) test to check whether the selected sand types and replacements statistically and significantly impacted the properties of mortar. Results revealed that the selected replacements statistically and significantly influenced the workability, compressive strength and flexural strength while no significant improvements were noticed with the workable life of mortars. Mortars with blended sand considerably improved the performance against capillary water absorption than mortar with river sand.
Keywords: river sand, manufactured sand, blended sand, fine aggregate, lime-cement mortar